Thermal, moisture and mechanical properties of Seacrete: A sustainable sea-grown building material. (10th January 2021) - Johra, Hicham; Margheritini, Lucia; Ivanov Antonov, Yovko; Meyer Frandsen, Kirstine; Enggrob Simonsen, Morten; Møldrup, Per; Lund Jensen, Rasmus
Highlights: Material characterization of low-voltage and high-voltage Seacrete materials. Mechanical resistance, thermal properties and water vapour sorption isotherms. Low-voltage Seacrete has material properties that are close to that of mortar. High-voltage Seacrete has higher porosity and moisture buffering capacity. High-voltage Seacrete has lower mechanical strength and thermal diffusivity. Abstract: The ever-increasing global demand for concrete engenders concerning sustainability issues. In addition to the large CO2 emissions induced by the production of cement, the fabrication of concrete requires important mining and excavation for the extraction of specific minerals, sand, and aggregates, which can endanger local ecosystems. Seacrete (also known as "Seament" or "Biorock") has previously been suggested as a potential alternative to traditional cementitious materials. Seacrete is artificial electrolytically precipitated calcium carbonate around a steel-frame cathode in which electrical current flows and that is submerged in seawater. Previous studies showed that it is ideal for the restoration of coral reefs and marine ecosystems. Furthermore, Seacrete is a very interesting sustainable concrete-like construction material for buildings and other human infrastructures. Indeed, it can be produced nearby all coastlines without any need for mining, extraction or transportation of additional material. In addition, the fabrication of Seacrete can easily be powered by low-intensity or local intermittent renewable energy sources. Previous publications pointed out that the mechanical properties and strength of Seacrete are similar to that of concrete, but no investigation has been conducted on other properties. For the first time, the current experimental study assesses the thermal and moisture properties of Seacrete. This article reports the density, compression strength, puncture resistance, specific heat capacity, thermal diffusivity, thermal conductivity, and water vapour sorption isotherms of two types of Seacrete, namely low-voltage and high-voltage Seacrete. Finally, this study emphasizes that all the aforementioned material properties of Seacrete are similar to that of concrete, confirming that the former can be considered for the construction of certain building elements and infrastructures.